(untitled) (Scientific journal of the Fergana State University, 2026)
This article analyses the opportunities for developing professional skills of prospective teachers through the use of an integrative approach in the educational process. The study examines methodological and communicative skills, as well as the significance of reflective competence. Within the literature review, the essence of integration models based on educational psychology, pedagogy methodology, and modern educational technologies is presented. In the practical section, methods for enhancing professional skills of future teachers are proposed through interactive teaching materials, interdisciplinary projects, and a mentoring system. The research results show the effectiveness of broad implementation of the integrative approach in teacher education.